A meshless projection iterative method for nonlinear Signorini problems using the moving Kriging interpolation. (January 2019) - Li, Xiaolin; Li, Shuling
Abstract: A meshless projection iterative method (MPIM) is developed in this paper for solving nonlinear Signorini problems. In the MPIM, a projection iterative method is adopted to linearize the nonlinear Signorini problem to a sequence of linear boundary value problems, and then the moving Kriging interpolation is used to solve these linear problems iteratively. The nonlinear inequality boundary conditions are treated efficiently by the projection iterative method, while the Dirichlet boundary condition is implemented directly with the help of the moving Kriging interpolation. Numerical results demonstrate the efficiency and convergence of the MPIM.